2001
DOI: 10.1039/b101369f
|View full text |Cite
|
Sign up to set email alerts
|

Diphosphines based on an inherently chiral calix[4]arene scaffold: synthesis and use in enantioselective catalysis

Abstract: C(O)NHCMe(Ph)H, 10) have been synthesised. The enantiomerically pure calixarenes 7, 8 and 10 having an AABC substitution pattern are inherently chiral. Reaction of the latter three diphosphines with [Pd(2-Me-allyl)(THF) 2 ]BF 4 (THF = tetrahydrofuran) afforded the chelate complexes [Pd(2-Me-allyl)(diphosphine)]BF 4 11-13, respectively, while reaction with [Rh(NBD)(THF) 2 ]BF 4 (NBD = norbornadiene) resulted in quantitative formation of the complexes [Rh(NBD)(diphosphine)]BF 4 14-16, respectively. As a result o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
68
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(69 citation statements)
references
References 34 publications
1
68
0
Order By: Relevance
“…Since the latter mechanism has been observed with O-substituted p-tert-butylcalix [6]arenes, [26] it is reasonable to assume that the lack of substitution on the phenol groups allows for rapid aromatic-through-the-annulus rotation and, hence, the apparent high symmetry observed is the result of fast interconversion between the different conformers. 4 indeed showed the compound adopting a cone conformation in solution, in which the four complexing arms are held together in closed proximity, thereby providing a suitable octadentate coordination site for lanthanide cations. [14] The X-ray crystal structure of the lutetium complex further showed that a water molecule was encapsulated in the cavity formed by the four dioxo-ethylene bridges (OϪC1ϪC2ϪO), with H-bonding interactions between this water molecule and the oxygen atoms.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the latter mechanism has been observed with O-substituted p-tert-butylcalix [6]arenes, [26] it is reasonable to assume that the lack of substitution on the phenol groups allows for rapid aromatic-through-the-annulus rotation and, hence, the apparent high symmetry observed is the result of fast interconversion between the different conformers. 4 indeed showed the compound adopting a cone conformation in solution, in which the four complexing arms are held together in closed proximity, thereby providing a suitable octadentate coordination site for lanthanide cations. [14] The X-ray crystal structure of the lutetium complex further showed that a water molecule was encapsulated in the cavity formed by the four dioxo-ethylene bridges (OϪC1ϪC2ϪO), with H-bonding interactions between this water molecule and the oxygen atoms.…”
Section: Resultsmentioning
confidence: 99%
“…The ether-amide substituent was designed so that it can act as a bidentate ligand forming a five-membered cycle upon coordination of its ether and amide functions to trivalent lanthanide ions Ln III . We have shown that A 4 bL 4 acts as an inorganic-organic receptor, encapsulating both a lanthanide ion and a solvent molecule. In addition, the crystal structure of the Lu III 1:1 complex shows the coordination cavity predisposed to further accommodate one water molecule hydrogen-bonded to the oxygen atoms of the phenol units, which rigidifies the induced cavity, and binds the metal ion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Matt has shown that a lower-rim, inherently chiral calixarene scaffold can be used in allylic alkylation (palladium) and hydrogenation (rhodium), though low ees were obtained. [4] Others have shown that cooperative effects may potentially be provided by supramolecular interactions involving the concave bowl. [5] However, a comprehensive picture has yet to emerge regarding application of directing effects in the bowl towards designing superior asymmetric catalysts for carrying out reactions rather than purely for recognition phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…For instance a tridifferentiated C 4 resorcinarene, with three different groups, was synthesized en route to superbowl containers 28 . Tridifferentiated calix(4)arenes were also synthesized as racemic mixtures because of their inherent asymmetry [29][30][31] . In the realm of molecules of higher symmetry, C 6 calix(6)arenes with three 32,33 or even four 34 functionalities (tetradifferentiated) have also been described albeit inherently as racemic mixtures.…”
mentioning
confidence: 99%